2018
DOI: 10.24272/j.issn.2095-8137.2017.048
|View full text |Cite
|
Sign up to set email alerts
|

肯尼亚Shimba山生态系统两栖爬行动物的生物地理学

Abstract: The Shimba Hills ecosystem along the south coast of Kenya is a key East African biodiversity hotspot. Historically, it is biogeographically assignable to the East African coastal biome. We examined the current Shimba Hills herpetofauna and their zoogeographical affinities to the coastal forests and nearby Eastern Arc Mountains biodiversity hotspots. The key studied sites included the Shimba Hills National Reserve, forest reserves, Kaya forests, and adjacent private land. Data on herpetofaunal richness were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Not only did it support feeding items but also gave more emphasis on their distributions in Eastern and Western African ecosystems in relation to observations respectively by Schiøtz (1975, 1999), Malonza et al. (2006, 2018), Malonza and Bwong (2023), Measey et al. (2009) and Vlok et al.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Not only did it support feeding items but also gave more emphasis on their distributions in Eastern and Western African ecosystems in relation to observations respectively by Schiøtz (1975, 1999), Malonza et al. (2006, 2018), Malonza and Bwong (2023), Measey et al. (2009) and Vlok et al.…”
Section: Discussionsupporting
confidence: 61%
“…Similarly with the current study, it is true because most species were found as predominantly insect and frog eaters. Not only did it support feeding items but also gave more emphasis on their distributions in Eastern and Western African ecosystems in relation to observations respectively bySchiøtz (1975Schiøtz ( , 1999,Malonza et al (2006Malonza et al ( , 2018,Malonza and Bwong (2023),Measey et al (2009) andVlok et al (2013).5 | CON CLUS IONSDue to the fact that observations of this current study showed anuran diversity and distribution in and around habitats in the study area, it may have generated and added to the baseline data for the anurans biodiversity in Kingwal Swamp and North Nandi Forest Reserve. Anuran biodiversity is a function of habitat diversity and season, with the associated differences in microhabitat structure that provide diverse niches and ways of exploring resources.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Baseline information on biodiversity is important in ecosystem management planning. Clarifying species distribution provides useful information on ecology, habitat preference, and species replacement (Goodman et al, 1996; Malonza et al, 2018; Stanley & Kihaule, 2016). Studies investigating the relationship between species richness and altitude have yielded diverse patterns (Taylor et al, 2015).…”
Section: Introductionmentioning
confidence: 99%